Study of the toxicity of the drug “Devivit Carnitine” during prolonged intragastric administration - Vus, U.; Gutyj, B.; Sachuk, R.; Kushnir, V. (Scientific Progress & Innovations, 2025)
The aim of this study was to investigate the toxicity of Devivit Carnitine in laboratory animals under conditions of prolonged intragastric administration. The animals received the preparation for 28 days in different doses, after which their clinical condition, morphological and biochemical blood parameters, and organ mass coefficients were evaluated. Throughout the experiment, no cases of death or signs of intoxication were observed in the rats. The animals remained active, maintained good appetite, which indicates the absence of any adverse effects of the preparation on behavioral reactions or general physiological state. Analysis of the organ mass coefficients showed that 28-day administration of Devivit Carnitine did not cause pathological changes in the mass of vital organs. A slight decrease in liver weight accompanied by an increase in the mass of kidneys, heart, and spleen can be regarded as an adaptive-compensatory response of the organism to the intake of biologically active components of the preparation that stimulate metabolic processes. Hematological parameters remained within physiological limits. A minor decrease in erythrocyte count, hemoglobin concentration, and platelet number was combined with an increase in leukocyte and granulocyte counts, indicating a mild stimulatory effect of the preparation on the cellular component of the immune system. The ratio of blood corpuscles remained within reference ranges, confirming the absence of hematotoxic effects. Biochemical analysis of blood revealed an increase in total protein, albumin, urea, triglycerides, and cholesterol concentrations, suggesting activation of protein and lipid metabolism under the influence of the preparation. At the same time, a decrease in the activity of transaminases (ALT, AST) and alkaline phosphatase, as well as a reduction in bilirubin concentration, were noted, indicating the absence of cytolytic processes in the liver and confirming the hepatoprotective properties of Devivit Carnitine. The maintenance of creatinine, calcium, phosphorus, and chloride levels within normal limits indicates normal kidney function and stability of the water – electrolyte balance. In general, the obtained results demonstrate that 28-day administration of Devivit Carnitine at different doses does not cause pathological changes in the functional state of laboratory animals. The detected alterations are of a physiologically adaptive nature and remain within normal ranges. The preparation exerts a mild stimulatory effect on protein and lipid metabolism and contributes to the optimization of hematological parameters.